Cobalt-Based Electrolytes for Efficient Flexible Dye-Sensitized Solar Cells. (19th February 2019) - Kim, Jihun; Lee, Horim; Kim, Dong Young; Kim, Sehyun; Seo, Yongsok
Abstract: We have developed new flexible dye-sensitized solar cells (DSSCs) comprising organic dye (JH-1), cobalt redox electrolyte and hierarchically structured TiO2 (HS-TiO2 ) photoelectrode prepared using an electrostatic spray method. The performance of JH-1 sensitized flexible DSSC with a cobalt redox electrolyte was compared with those of N719-based DSSC and DSSC with I - / I3 - redox electrolyte. As a result, JH-1 sensitized flexible DSSC with [Co(Ⅲ/Ⅱ)(bpy-pz)3 ](PF6 )3/2 redox system exhibited a high photocurrent density of 9.17 mA cm -2, an open circuit voltage of 0.953 V, a fill factor of 0.70, and a power conversion efficiency of 6.12% under 1 sun illumination (100 mW cm -2 ). The incident photon-to-current conversion efficiency was measured to explain the photocurrent generation difference by different dyes and electrolytes. The electron recombination lifetime of cells was measured by intensity-modulated photovoltage spectroscopy. Mass transport in DSSCs employing cobalt redox electrolytes was also investigated by the photocurrent transient measurements and electrochemical impedance spectroscopy (EIS) analysis.